Bat population dynamics: multilevel model based on individuals' energetics - Paula Federico; Dobromir T. Dimitrov; Gary F. McCracken (Mathematical Biosciences and Engineering)
Temperate-zone bats are subject to serious energetic constraints due to their high surface area to volume relations, the cost of temperature regulation, the high metabolic cost of flight, and the seasonality of their resources. We present a novel, multilevel theoretical approach that integrates information on bat biology collected at a lower level of organization, the individual with its physiological characteristics, into a modeling framework at a higher level, the population. Our individual component describes the growth of an individual female bat by modeling the dynamics of the main body compartments (lipids, proteins, and carbohydrates). A structured population model based on extended McKendrick-von Foerster partial differential equations integrates those individual dynamics and provides insight into possible regulatory mechanisms of population size as well as conditions of population survival and extinction. Though parameterized for a specific bat species, all modeling components can be modified to investigate other bats with similar life histories. A better understanding of population dynamics in bats can assist in the development of management techniques and conservation strategies, and to investigate stress effects. Studying population dynamics of bats presents particular challenges, but bats are essential in some areas of concern in conservation and disease ecology that demand immediate investigation.